A Study of the Use of Nonacademic Factors in Holistic Undergraduate Admissions Reviews. (2nd November 2019) - Hossler, Don; Chung, Emily; Kwon, Jihye; Lucido, Jerry; Bowman, Nicholas; Bastedo, Michael
ABSTRACT: How colleges make admissions decisions at four-year institutions is facing high levels of scrutiny. Students, families, and policymakers are asking how offices of admissions decide to admit students. Increasing numbers of institutions are becoming test optional and/or using holistic admissions schemes, but little is known about how decisions are made. This exploratory study employs three modes of research to examine the use of nonacademic factors in admissions. The methodological approaches include: a qualitative meta-analysis of empirical and models of classificatory frameworks for assessing nonacademic factors in admissions, 19 qualitative interviews at 10 public and private institutions across a range of selectivity, and the analysis of relevant survey data from over 300 admissions professionals. Results indicate academic factors including grades, test scores, and rigor of courses were the most important considerations for admissions. The second most important were contextual: the use of student, family, and school background characteristics. The final set of factors used were nonacademic; the most commonly used were measures of student performance and attitudinal factors. Institutional selectivity and public or private control also had an impact on the relative importance of these factors.